K-Modes with Binary Logistic Regression: An Application in Marketing Research - Rebolledo, Jonathan; Rodríguez Aguilar, Román (Springer, 2023)
Binary logistic regression is a statistical method used to analyze data with binary outcome variables. It is a type of generalized linear model (GLM) and is often used in fields such as medicine, psychology, and sociology. Using this model with some degree of data noise might give wrong results. ©2023 Springer, The authors.